Case Report: A case of Dubin-Johnson syndrome in a newborn - Long, Junshan; Qiu, Baowei; Su, Xiaoxia; Zhang, Jing; Dong, Qi (Frontiers in Pediatrics, 2024)
Background Dubin-Johnson Syndrome (DJS) is a rare autosomal recessive genetic disorder, with most cases presenting in adolescence, but rare in newborns. Objective To investigate the clinical characteristics and treatment outcomes of DJS in a newborn. Methods We present the clinical features of a newborn diagnosed with DJS through molecular genetic testing. Results The patient was a male newborn who developed jaundice and scleral icterus on the 6th day of life. Both direct and indirect bilirubin levels were elevated. After treatment with phototherapy, indirect bilirubin levels decreased, but direct bilirubin remained unchanged, and the stool color gradually lightened. At 56 days of age, the patient underwent laparoscopic cholecystostomy, which revealed viscous bile plugs in the bile ducts. Following the surgery, the patient received oral ursodeoxycholic acid, compound glycyrrhizin, and methylprednisolone. Follow-up until one year post-surgery showed a gradual reduction in direct bilirubin levels to the normal range. Molecular genetic testing revealed three heterozygous mutations in the ABCC2 gene on chromosome 10, with one pathogenic variant inherited from the father and two from the mother, confirming the diagnosis of DJS. Conclusion DJS is a benign condition with a favorable prognosis. In newborns, it should be differentiated from other causes of cholestasis, and compared to cholestasis, jaundice in newborns with DJS responds more slowly to treatment.